1997
DOI: 10.1021/bi9709497
|View full text |Cite
|
Sign up to set email alerts
|

S-Acylation and Plasma Membrane Targeting of the Farnesylated Carboxyl-Terminal Peptide of N-ras in Mammalian Fibroblasts

Abstract: We have used a series of fluorescent lipid-modified peptides, based on the farnesylated C-terminal sequence of mature N-ras [-GCMGLPC(farnesyl)-OCH3], to investigate the membrane-anchoring properties of this region of the protein and its reversible modification by S-acylation in cultured mammalian fibroblasts. The farnesylated peptide associates with lipid bilayers (large unilamellar phospholipid vesicles) with high affinity but in a rapidly reversible manner. Additional S-palmitoylation of the peptide suppres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
95
0
5

Year Published

1998
1998
2004
2004

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 134 publications
(111 citation statements)
references
References 52 publications
11
95
0
5
Order By: Relevance
“…We and others have demonstrated that short peptide sequences are sufficient to direct the addition of both lipids and confer plasma membrane targeting (Schroeder et al, 1996(Schroeder et al, , 1997Wolven et al, 1997) (this study). Biophysical measurements of the association of lipid-modified peptides with artificial bilayers provide a rationale for the requirement of two lipid modifications in targeting proteins to membranes (Peitzsch and McLaughlin, are targeted to the plasma membrane via their association with Gpa1p, which is dually acylated.…”
Section: Plasma Membrane-targeting Via Lipid Modifications and Proteimentioning
confidence: 56%
“…We and others have demonstrated that short peptide sequences are sufficient to direct the addition of both lipids and confer plasma membrane targeting (Schroeder et al, 1996(Schroeder et al, , 1997Wolven et al, 1997) (this study). Biophysical measurements of the association of lipid-modified peptides with artificial bilayers provide a rationale for the requirement of two lipid modifications in targeting proteins to membranes (Peitzsch and McLaughlin, are targeted to the plasma membrane via their association with Gpa1p, which is dually acylated.…”
Section: Plasma Membrane-targeting Via Lipid Modifications and Proteimentioning
confidence: 56%
“…The main function of protein palmitoylation is to facilitate membrane binding of the palmitate-modified proteins. Although other fatty acid modifications also increase protein hydrophobicity, those modifications result in only transient membrane association (t 1/2 p1 min) (Schroeder et al, 1997). Furthermore, proteins that undergo palmitoylation in conjunction with either myristoylation or prenylation demonstrate an even stronger membrane association with a t 1/2 >70 h (Alland et al, 1994;Shahinian and Silvius, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…To date direct determination of the membrane-binding properties of biologically functional proteins has focused on acylated and isoprenylated peptides and proteins (9)(10)(11)(12)(13)(14)(15)(16), whereas there is a gap for sterol-modified peptides and proteins.…”
mentioning
confidence: 99%